Wilkie syndrome as a cause of upper intestinal obstruction and its minimally invasive surgical management: a case report and review of the literature - Ferraez-Pérez, Jaime A.; Farah-Osorio, Salvador; Medina-Medina, Jorge A.; Ávalos-Abreu, Rodolfo O.; Osorio-Euán, Alejandro; Cab-Serrano, Barbara P.; Torres-Valdés, Eduardo A.; Ayuso-Díaz, Victor M.; Moreno-Enríquez, Angelica; Noguera-Echeverría, Alexis E. (International Journal of Research in Medical Sciences, 2025)
Upper bowel obstruction is a diagnostic and therapeutic challenge due to the proximity of vascular structures and the anatomical constraints imposed by the thorax. Wilkie syndrome, a rare cause of upper GI obstruction, is associated with severe aortomesenteric compression and is usually diagnosed in children and adolescents. We present the case of an 18-year-old male patient with postprandial fullness, recurrent vomiting and epigastric pain. Contrast tomography showed severe gastric dilatation, a reduced aortomesenteric angle (11°) and an aortomesenteric distance of 3 mm, confirming the diagnosis. Endoscopy showed signs of gastric ischaemia with suspected perforation. Emergency diagnostic laparoscopy was performed and gastric perforation with mediastinal communication and duodenal ischaemia was identified. A partial gastrectomy with latero-lateral duodeno-jejunal anastomosis was performed. The postoperative course was favourable with tolerance to diet on day 3 and no complications at 3 months follow-up. Laparoscopic surgery represents a safe and effective alternative in the management of Wilkie’s syndrome, reducing morbidity and optimising postoperative recovery.